Influence of the Blended Learning Method on Student Achievement in Mathematics Lessons - Baso Intang Sappaile; Dina Mayadiana; Rino Lengam; Xie Guilin; Muhammad Ichsan Abda (Yayasan Adra Karima Hubbi, 2024)
Background. The characteristics and achievements of each student are different. This is influenced by the methods, interests, talents, media, sources, environment, and even strategies of the students themselves. A blanded learning method that combines traditional classroom learning with online-based learning can make a big impact in the world of education. It will provide opportunities for students to learn with more flexibility. It also creates a more engaging learning experience. Purpose This study aims to find out how much the use of blended learning method affects students' achievement. This achievement is more specific to mathematics learning. This is because there are often difficulties in understanding mathematics learning by students. Therefore, the blended learning method is considered to be able to influence learning, especially mathematics. Method. The method used in this research is quantitative. This method is considered suitable as a measuring tool. This is because the effect of using the blanded learning method on student achievement can be measured by a number scale. So that it can be read or understood through graphs, percentages, or data processing. Research using quantitative methods that have the characteristics of using numbers will be more in line with this research. Results. The result of this study explains that the use of blanded learning method will affect students' achievement in learning mathematics. The blanded learning method that combines traditional and online-based learning will enrich the learning experience. Not only that, this method will also provide a combination of different methods, media, sources, environments, and even learning strategies. Conclusion This research can be concluded that the use of blanded learning method will provide innovation in learning. It will support different ways of learning from students. In addition, it will also help teachers in the flexibility of organising learning time. On the other hand, it will also help students who have difficulty in following face-to-face learning.